Exploring the dynamic nexus between cross-border dollar claims and global economic growth - Alexiou, Constantinos; Vogiazas, Sofoklis; Benbow, Alex (MDPI, 2024)
This paper addresses the role of the U.S. dollar in fostering global economic growth during the post-war period. The existing literature lacks a comprehensive understanding of the true implications of the U.S. dollar’s status as a reserve currency and a dearth of studies examining its impact. In this study, we explore the dynamic long-run and short-run relationships between cross-border U.S. dollar claims, global GDP, and global trade while gauging the impact of the Global Financial Crisis (GFC) and the COVID-19 pandemic. In doing so, we use ARDL methodology for a data set that spans the period of 1980 to 2022. The estimation results reveal a robust long-run relationship between U.S. dollar claims, global GDP and global trade and no clear evidence of asymmetric effects. Our findings are of great significance for monetary authorities, emphasising the need for a nuanced understanding of the implications of the U.S. dollar’s conducive role in shaping global economic dynamics and fostering growth.
Keywords: eurodollar; cross-border dollar claims; economic growth; global trade